Electromagnetic Metamaterials Modern Insights into Macroscopic Electromagnetic Fields - Sakoda, Kazuaki; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents novel and fundamental aspects of metamaterials, which have been overlooked in most previous publications, including chirality, non-reciprocity, and the Dirac-cone formation. It also describes the cutting-edge achievements of experimental studies in the last several years: the development of high-regularity metasurfaces in optical frequencies, high-performance components in the terahertz range, and active, chiral, nonlinear and non-reciprocal metamaterials in the microwave range. Presented here are unique features such as tunable metamaterials based on the discharge plasma, selective thermal emission from plasmonic metasurfaces, and the classical analogue of the electromagnetically induced transparency. These most advanced research achievements are explained in understandable terms by experts in each topic. The descriptions with many practical examples facilitate learning, and not only researchers and experts in this field but also graduate students can read the book without difficulty. The reader finds how these new concepts and new developments are being utilized for practical applications.
Modern Insights into Macroscopic Electromagnetic Fields -- Fabrication Techniques for Three-dimensional Optical Metamaterials -- Blackbody Metamaterial Composite Film of Nanoparticle and Polymer -- Bottom-up Strategies for Fabricating Meta-atoms via Self-assembly of Polymers and Nanoparticles -- UV-Nanoimprinted Metasurface Thermal Emitters for Infrared CO2 Sensing -- Birefringent Metamaterials for THz Optics -- Development and Applications of Metasurfaces for Terahertz Waves -- Efficient Optical Modulation of Terahertz Metamaterials Utilizing Organic/Inorganic Semiconductor Hybrid Systems -- Negative Refractive Index Materials Composed of Metal Patterns and the Applications -- Functional Composites of Discharge Plasmas and Solid Metamaterials -- Meta-Atoms Emulating Quantum Systems -- Dispersion Relation in Chiral Media: Credibility of Drude-Born-Fedorov Equations -- Surface Waves of Isotropic Chiral Metamaterials -- Magnetochiral Metamolecules for Microwaves -- Dispersion Engineering of Nonreciprocal Metamaterials -- Photonic Dirac Cones and Relevant Physics.
Keywords: Optical materials; Magnetism; Telecommunication; Optical Materials; Magnetism; Microwaves, RF Engineering and Optical Communications